Improving the Efficiency and Effectiveness of Learning for Students of Tadris Social Studies Program at UIN Syarif Hidayatullah Jakarta with Artificial Intelligence - Zaharah, Zaharah; Fajarini, Ulfah; G.I, Kirilova; Sina, Ibnu; Basyit, Abdul (Sosio-Didaktika: Social Science Education Journal, 2024)
In this digital period, technological advancement is growing fleetly, including in the field of artificial intelligence( AI). AI has entered colorful aspects of life, including Education. In Education, AI offers colorful openings to ameliorate the effectiveness and effectiveness of pupil literacy. scholars are faced with colorful complex literacy tasks and demands. This frequently makes it delicate for them to manage their time and complete tasks meetly. Artificial intelligence( AI). comes as a result to help scholars complete their tasks more fluently, efficiently and effectively. This study aims to dissect the effectiveness and effectiveness of pupil literacy using artificial intelligence, and to identify the benefits and challenges of using AI in education. This study uses a quantitative descriptive system with primary and secondary data sources, with data collection procedures and interviews, and giving doubters to 104 Repliers using a Likert- Scale, Data Analysis with Data Presentation, Data Reduction and conclusions. The exploration was conducted at Syarif Hidayatullah State Islamic University, Jakarta, as Student- Repliers in Semester IV in the Social Studies Education- Programs. The results of this study indicate, the use of artificial intelligence( AI) can increase the effectiveness and effectiveness of pupil literacy in the social study- program, as substantiated by the results of doubters from repliers, that55.8 of the repliers are effective in the use of artificial intelligence( AI) and can increase effectiveness by51.9 and40.4 of the use of AI is applicable in perfecting understanding of lecture material, and52.9 of the use of AI is suitable to overcome time constraints in completing lecture assignments. This exploration is anticipated to make a precious donation to the development of education in the digital period and to help scholars to learn more effectively and efficiently. give recommendations for the wise and responsible use of artificial intelligence( AI) in education. Flash back AI is only an adjunct for druggies, not a cover for doing anything including lecture assignments